FLEXIBILITY OF ISLAMIC NORMS IN GUIDING PEOPLE’S MORALITY IN THEIR REAL LIVES - Sumedi Sumedi (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
The purpose of this research is to analyze the the essense of Islamic norm guiding the human being’s morality as long as he lives as a mukallaf in order to let the public know that Islamic teaching especially related to morality is very flexible, elastic, and adjustable to the real condition of everyone. So far the problem in relation to morality is its criteria of morality and of immorality. In genelal people know that the criteria of morality may be based on religion or humanism. It seems thjat people need the scientific, rather than natural, criteria as an alternative. The methods used in this research is qualitative based on the data collected from the various sources. The result of the research is that the Islamic norm of morality is flexible and its flexibility is shown by the principle that any behaviour can be said as good attitude if its advantages are more and bigger than its disadvantages both in this world and in the hereafter. The elements of Islamic morality-and-immorality are four: namely intention, deed, mukallaf and belief or disbelief. The four elements of morality may exist in everyone at any place and at any time. The Islamic morality is determined by the existence of belief and the three other elements. Without belief especially in God’s Oneness and in the existence of the hereafter, although there are three other elements which are the same as those existing in a believer, the Islamic morality cannot exist or appear although some people may judge that it is good attitude.